Study on regional contrast in development of agricultural mechanization in Zhejiang province based on GIS - ZHENG Wen-zhong; HE Yong (浙江大学学报. 农业与生命科学版)
Aiming at imbalance and regionalization in development of agricultural mechanization, assessment indexes and models were put forward. Accordingly, geographical information system (GIS, Map-Info) with powerful function of both mapping visualization and spatial analysis was combined with assessment models. For 69 counties in Zhejiang province, China taken as basic assessment units, results of assessment were mapped and their spatial distribution was analyzed with congruence of thematic map. Then, measures for promoting development of agricultural mechanization were suggested.